Career decision-making difficulties of Turkish adolescents - Bacanli, Feride (International journal for educational and vocational guidance, 2016)
The purposes of this study are (1) to adapt the Career Decision-Making Difficulties Questionnaire (CDDQ) to Turkish high school students and (2) to examine gender differences, grade differences, and differences between “decided” and “undecided” students. The sample consisted of 2509 adolescent students. The results showed that the structure of the Turkish version of the CDDQ was similar to the structure of the original CDDQ. The adolescent girls reported greater difficulties general indecisiveness, and dysfunctional belief difficulties than adolescent boys. Adolescent boys reported greater motivation difficulties than adolescent girls. Undecided students reported having more difficulties than decided students.